PENGARUH MOTIF MENONTON ACARA INDONESIA LAWAK KLUB TRANS 7 TERHADAP KEPUASAN HIBURAN MASYARAKAT KELURAHAN SIMPANG BARU KECAMATAN TAMPAN PEKANBARU - Erma Fatma; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The media has a huge influence on the direction of public life, as the mean of the mass media itself that the media specifically designed to reach a very wide community. The type of media traditionally known like newspapers, magazines, radio, and television. The needs of the audience will fulfilled by the existence of the shows that are presented by the media. In accordance with the uses and gratification theory which explains about the freedom in choosing which media that audiences are considered to be able to meet their needs after consuming media. Where in theory there are concepts of measuring satisfaction i.e Sought Gratification (Motif) and Gratification Obtained (Satisfaction). Sought Gratification is a motive as the background in using the media, while Gratification Obtained is a real satisfaction obtained after using the media.The method used in this research is quantitative method with a survey of explanation, the researcher collected data using questionnaires. The location of this research is in the village of Simpang Baru village Tampan sub district Pekanbaru. The number of samples for this study were 96 respondents obtained from the Unknow Populations formula , and the sampling itself using accidental sampling technique. To find out how much the relationship between the two variables, the researcher use Person Product Moment correlation analysis. For the questionnaire data processing, using Statistics Program Product Of Service Solution (SPSS) Windows version 17.These results indicate that the motif effect of watching Indonesia Lawak Club Trans 7 show entertainment satisfaction from the society of Simpang Baru village Tampan sub district Pekanbaru, that the value of R = 0.801 and the coefficient of determination (R square) is approximately 0,641 result of squaring the correlation coefficient of 0.343 x 0.343 with 0.001 significance level smaller than α = 0.05. The figure mean that the contribution of the effect upon the satisfaction motif variables obtained amounted to 64.1% with strong influence category.Keywords: Mass Media, Entertainment, Theory Uses And Gratifications, Motif, Satisfaction, Indonesia Lawak Club Trans 7 Show.